Emerging big data in medicinal chemistry: promiscuity analysis as an example - Bajorath, Jürgen; Hu, Ye (Henry Stewart Talks, 2018)
Big data criteria in medicinal chemistry, Data at varying confidence levels, Promiscuity and polypharmacology, Compound promiscuity analysis in light of big data criteria, Promiscuity of screening hits, Promiscuity across major target families, Promiscuity of kinase inhibitors